Verbal and non-verbal communication strategies in English as a business lingua franca (BELF) / Seval Birlik - Seval , Birlik (2018)
This study examines the use of English as Business Lingua Franca (BELF) and its impact to a successful and effective intercultural communication. This study argues that verbal and non-verbal communication strategies in BELF may contribute to the overall success in intercultural business interactions. To understand how BELF speakers manage to communicate successfully and effectively in intercultural business communication, the theoretical framework Community of Practice (CofP) was applied to determine the external context of the interactions. Conversation Analysis (CA) was used as the analytical framework. The study draws on a survey, audio recorded semistructured interviews and video recorded meetings. The focus of the study lies on the meeting data. The findings of the study reveal four common verbal communication strategies (VCS) labeled as ‘questioning, repeating, reformulating, and explaining’ strategies and three non-verbal communication strategies (NVCS) categorized as ‘head movements, hand movements and eye contact and gaze’. It shows that VCS and NVCS were employed as part of the meeting participants’ shared repertoire and resources to manage intercultural communication successfully by facilitating negotiation of meaning and thus shared understanding. The study also reveals external factors that contribute to BELF success based on interview results. It was noted that developing a shared repertoire in the specific business community through the experience of working together, thus knowing the specific ‘working culture(s)’ and business context as well as considering the individual factors, played a crucial role in making the communication successful. The findings of this study provide an empirical basis regarding forms and functions of BELF and shed light on communicative competence and intercultural awareness of BELF users.